2006
DOI: 10.1021/jf061521u
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide Dissipation after Repeated Field Application to a Northern Thailand Ultisol

Abstract: Nontarget effects of pesticides may occur when the active ingredients have a long persistence in the environment. The half-lives of six insecticides commonly used in Thai fruit orchards under tropical field conditions were determined. A mixture of endosulfan-alpha and -beta, chlorpyrifos, malathion, dimethoate, and mevinphos was applied five times in 10-day intervals onto an Ultisol (lychee plantation ground-covered with grass vegetation, northwestern Thailand). On days 1, 3, 5, 7, and 10 after each applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
3
34
1
1
Order By: Relevance
“…Under lab conditions (30°C and a water content of 32% by weight), the average half‐life of methomyl in the topsoil was 15.5 d, which is in the range of published values (Extoxnet, 1996). Under field conditions, however, at the same research site Ciglasch et al (2006) found significantly decreased field half‐lives of several pesticides compared with published values. Therefore, we might expect a faster decay of methomyl and chlorothalonil.…”
Section: Resultsmentioning
confidence: 46%
“…Under lab conditions (30°C and a water content of 32% by weight), the average half‐life of methomyl in the topsoil was 15.5 d, which is in the range of published values (Extoxnet, 1996). Under field conditions, however, at the same research site Ciglasch et al (2006) found significantly decreased field half‐lives of several pesticides compared with published values. Therefore, we might expect a faster decay of methomyl and chlorothalonil.…”
Section: Resultsmentioning
confidence: 46%
“…Agrochemicals are increasingly contributing to water quality degradation in upland agriculture areas where swiddening was once prevalent, for example in the Mae Sa catchment in northern Thailand (Ciglasch et al 2005(Ciglasch et al , 2006Kahl et al 2008), Inle lake in Myanmar (Sidle et al 2007), and potentially, the Cameron Highlands of Malaysia (cf. Ismail et al 2004;Mazlan and Mumford 2005).…”
Section: Water Qualitymentioning
confidence: 99%
“…Konda and PĂĄsztor (2001) obtained a 33% decrease for the level of 0-5 cm at the end of 14 days, in a field study for soils from the Luvisol order in Hungary, in the context of precipitation (approximately 25 mm on average for the period of the study), a situation that would be in agreement with what was obtained in the treatment with greater irrigation in the present study. On the other hand, other authors have found that in tropical soils (Ultisol) CHP recovery at a depth of 0-10 cm was 23.6% (Ciglasch et al, 2006); a situation that shows a high decrease of initially applied AI, associated with moisture and precipitation during the assay. At the depth of 20-30 cm, the values of the decrease in AI were 5.6, 9.3 and 13.1% of the concentration found at the surface of the column, from the control to the treatment with the greatest flow, respectively, which shows some influence of excess water on the vertical movement of CHP.…”
Section: Distribution Of Chp Residues In the Soilmentioning
confidence: 84%